TEACH: A Framework for Recovery-Oriented Education and Training - Abraham , Rudnick (International Journal of Psychosocial Rehabilitation, 2016)
Recovery-oriented services for people with mental illness are best practices, yet related education and training is not well developed. This article highlights an approach – TEACH (Theory, Evidence, Action in Care for Health) – to facilitate recovery-oriented education and training. Research about TEACH and other recovery-oriented education and training approaches is needed.